IMPLEMENTASI KURIKULUM MERDEKA DENGAN PENDEKATAN (DEEP LEARNING) PADA MATA PELAJARAN AGAMA ISLAM DI SMKN 3 BUDURAN - Insan Falih; Ainun Nadlif (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This study aims to describe the implementation of the Merdeka Curriculum with a deep learning approach in Islamic Religious Education (PAI) at SMKN 3 Buduran through the POAC (Planning, Organizing, Actuating, and Controlling) framework. The method used was descriptive qualitative with data collection techniques in the form of observation, interviews, and documentation. The results of the study show that: (1) Planning includes understanding the Merdeka Curriculum paradigm, developing intracurricular and cocurricular tools, and teacher participation in training. (2) Organization is carried out by the principal and vice principal of curriculum as facilitators. (3) Implementation focused on differentiation strategies, integration of religious values, and co-curricular activities, but was constrained by differences in student abilities and time limitations. (4) Control was carried out through supervision, evaluation of facilities and infrastructure, teacher performance, and the formation of 8 graduate profiles. In general, the implementation of the Merdeka Curriculum at SMKN 3 Buduran is going well with the support of the school's commitment and teacher involvement, despite still facing technical obstacles and variations in student abilities.